Understanding the survival of Zika virus in a vector interconnected sexual contact network - Ferdousi, Tanvir; Cohnstaedt, Lee W.; McVey, D. Scott; Scoglio, Caterina M. (My University, 2019)
The recent outbreaks of the insect-vectored Zika virus have demonstrated its potential to be sexually transmitted, which complicates modeling and our understanding of disease dynamics. Autochthonous outbreaks in the US mainland may be a consequence of both modes of transmission, which affect the outbreak size, duration, and virus persistence. We propose a novel individual-based interconnected network model that incorporates both insect-vectored and sexual transmission of this pathogen. This model interconnects a homogeneous mosquito vector population with a heterogeneous human host contact network. The model incorporates the seasonal variation of mosquito abundance and characterizes host dynamics based on age group and gender in order to produce realistic projections. We use a sexual contact network which is generated on the basis of real world sexual behavior data. Our findings suggest that for a high relative transmissibility of asymptomatic hosts, Zika virus shows a high probability of sustaining in the human population for up to 3 months without the presence of mosquito vectors. Zika outbreaks are strongly affected by the large proportion of asymptomatic individuals and their relative transmissibility. The outbreak size is also affected by the time of the year when the pathogen is introduced. Although sexual transmission has a relatively low contribution in determining the epidemic size, it plays a role in sustaining the epidemic and creating potential endemic scenarios.
Citation: Ferdousi, T., Cohnstaedt, L. W., McVey, D. S., & Scoglio, C. M. (2019). Understanding the survival of Zika virus in a vector interconnected sexual contact network. Scientific Reports, 9(1), 7253. https://doi.org/10.1038/s41598-019-43651-3